Dental education of outreach kindergarten service on parental dental knowledge - Ms Guofang Sun; Prof. Chun Hung Chu; Prof. Edward Chin Man Lo; Dr. Duangporn Duangthip (Elsevier, 2023)
Aim or Purpose: The aim is to evaluate the effect of oral health education (OHE) of an outreach service on the dental knowledge of kindergarten children's parents. Materials and Methods: The 6-month prospective study recruited kindergarten children's parents for a self-administered questionnaire survey at baseline. The questionnaire consisted of 16 multiple-choice questions on the cause and prevention of dental diseases to assess parents' dental knowledge. One point was given for each correct answer, and no point was given for a wrong answer or a 'don't know' answer. Thus, the dental knowledge score ranged from 0 to 16. The parents' dental knowledge was determined to be poor (scored 0-7), moderate (scored 8-12), or good (scored 13-16). Dental knowledge information leaflets and an OHE seminar were provided to the parents after the baseline survey. The questionnaire was used to re-assess the parents' dental knowledge after 6 months. The change in dental knowledge after the OHE was assessed using Wilcoxon signed rank tests. Results: Out of 757 parents, 620 remained in the program at the 6-month follow-up. At baseline, 7%, 69%, and 24% of parents exhibited poor, moderate, and good dental knowledge, respectively. Whereas after six months, 7%, 62%, and 31% of parents exhibited poor, moderate, and good dental knowledge, respectively. There was a significant difference between the proportions of parents with poor, moderate, and good dental knowledge before and after the program (Wilcoxon signed-rank test, P = 0.01). Conclusions: OHE of an outreach kindergarten service improved the dental knowledge of preschool children's parents.